A Critical Discourse Analysis of Presidents’ Inaugural Speeches in Indonesia: A Fairclough Perspective - Purwaningrum, Prapti Wigati; Harmoko, Danang Dwi (LPPM Universitas Bina Sarana Informatika, 2025)
Penelitian ini bertujuan untuk menelaah hubungan antara bahasa dan struktur sosial budaya dengan membandingkan teks pidato perdana Presiden Joko Widodo (2014) dan Prabowo Subianto (2024) melalui perspektif Analisis Wacana Kritis Fairclough. Penelitian ini berupaya menjawab tiga pertanyaan: (1) bagaimana pilihan kebahasaan digunakan untuk merepresentasikan visi politik kedua presiden? (2) ideologi apa yang terkandung dalam pidato mereka? dan (3) bagaimana praktik wacana mencerminkan konteks sosial-budaya yang lebih luas? Hasil penelitian menunjukkan bahwa pidato perdana Joko Widodo merefleksikan ideologi nasionalisme populis melalui penekanan pada kerja keras, gotong royong, dan persatuan yang menekankan kolektivitas dan inklusivitas. Sebaliknya, pidato Prabowo Subianto mengandung ideologi reformisme otoritatif yang ditandai dengan wacana pemberantasan korupsi, swasembada pangan, dan “demokrasi santun” untuk membangun legitimasi melalui bahasa ketertiban, otoritas moral, serta kedaulatan bangsa. Dengan demikian, pidato perdana tidak hanya menyajikan arah kebijakan, tetapi juga membangun posisi ideologis yang memengaruhi legitimasi politik kepemimpinan masing-masing. This study aims to examine the relationship between language and socio-cultural structure by comparing the inaugural speeches of President Joko Widodo (2014) and Prabowo Subianto (2024) through the lens of Fairclough’s Critical [ll1] Discourse Analysis. The research seeks to answer the following questions: (1) How are linguistic choices used to represent the leaders’ political vision? (2) What ideologies are embedded in their speeches? and (3) How do discourse practices reflect broader socio-cultural contexts? The findings indicate that Joko Widodo’s inaugural address foregrounded the ideology of populist nationalism through emphasis on “hard work,” “mutual cooperation,” and “unity,” reflecting an image of collective struggle and inclusivity. In contrast, Prabowo Subianto’s speech articulated an ideology of authoritative reformism, marked by discourses of corruption eradication, food self-sufficiency, and “polite democracy,” which positioned him as a strong leader seeking order, moral authority, and national sovereignty. While Jokowi’s discourse leaned toward constructing solidarity among the people, Prabowo’s discourse sought legitimacy through the language of discipline and protection of national dignity. These results demonstrate that inaugural speeches not only present policy directions but also construct ideological positions that shape political legitimacy.